Analisis Hubungan Stress Kerja dengan Keluhan Muskuloskeletal terhadap Kinerja Karyawan PT. Maruki Internasional Indonesia Makassar - Ika Triwati; Hardianty; Arman A (PT.Mantaya Idea Batara, 2022)
This research is an analytic observational study which was examined with a cross sectional study design. The relationship between work stress and musculoskeletal complaints on the performance of employees of PT. Maruki International Indonesia Makassar has been analyzed. There are 3 variables in this study, work stress as the independent variable, musculoskeletal complaints as the intervening variable, and employee performance as the dependent variable. The results indicate that there is no significant correlation between work stress and musculoskeletal complaints measured in employees of PT. Maruki International Makassar with p value = 0.391 and correlation value of 0.087. The same results are also shown in the correlation of work stress with the performance of employees of PT. Maruki International Indonesia Makassar with p value = 0.272 and correlation value of -0.102. Therefore, it can be concluded that there is no correlation between work stress and musculoskeletal complaints on the performance of PT. Maruki International Indonesia Makassar.